Relevance Profitability and Managerial Ownership Trough Capital Structure for Company Value - Icasania Septentia; Dwi Suhartini (Journal of Economics, Business, and Government Challenges, 2020)
The company has a goal of achieving going concern and making a profit. Companies that apply economic principles are generally not only oriented towards achieving maximum profit, but also trying to increase the value of the company and the prosperity of their owners. The company's objectives can be achieved by maximizing profitability by with the mechanism of Good Corporate Governance and also considering the selection of an appropriate capital structure to achieve corporate value. This study aims to determine the effect of profitability and managerial ownership on company value with capital structure as an intervening variable. This research sample of 13 food and beverage companies listed on the Stock Exchange in the 2012-2018 observation period. Testing the research hypothesis using the Partial Least Square (PLS) analysis technique. The results showed that profitability negatively affected capital structure and company value. Managerial ownership does not affect the capital structure or company value. Capital structure variables can mediate the effect of profitability on company value, but cannot mediate the effect of managerial ownership on company value